Optimización de las habilidades visuales mediante el entrenamiento visual deportivo. Revisión bibliografica - Acevedo Vásquez, Olga Lucia (Universidad Antonio Nariño, 2021)
Sports visual training is an area of optometry that was born in the early 20th century in the United States. This has its bases based on orthoptics. With sports visual training, what is sought is to enhance the visual abilities of different athletes by creating and applying a training program designed to correct, improve and enhance the different visual abilities. Objective: to identify the changes that occur in visual skills after visual sports training. Methodology: this work was carried out by means of a bibliographic review in databases such as ScIELO, PudMed and Sciencedirect, between the years 2000 and 2020. Results: it was evidenced that there are significant changes in some visual abilities such as stereiopsis, sacdic movements, visual reaction and eye-hand coordination. However, it was evidenced that not all articles achieved improvements in stereiopsis and visual reaction time. Conclusions: it was possible to show that visual sports training achieves improvements in visual skills in short periods of time, if personalized and specific protocols are implemented for each athlete.